THE INFLUENCE OF GREEN MARKETING AND DIGITAL MARKETING ON CUSTOMER LOYALTY IN CHICKEN INTESTINE CHIPS MSMEs IN KEDIRI - Sumelvia Dewi, Anita; Sudarmiatin, Sudarmiatin; Syahputra, Erwin (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
The problem addressed in this research concerns marketing management, focusing on the impact of green marketing and digital marketing on customer loyalty. The objective is to determine and analyze the effects of green marketing and digital marketing on customer loyalty both individually and collectively. This study uses a quantitative approach, with a population consisting of customers of chicken intestine chips MSMEs in Kediri. The sample includes 85 respondents. Data collection was conducted using questionnaires, and data analysis involved validity, reliability, classical assumption tests, multiple linear regression tests, and hypothesis testing. The research hypotheses testing revealed that green marketing has a significant partial effect on customer loyalty, digital marketing also has a significant partial effect on customer loyalty, and both green marketing and digital marketing have a significant simultaneous effect on customer loyalty in chicken intestine chips MSMEs in Kediri. Overall, this study contributes to the existing body of knowledge in marketing management by shedding light on the effects of green marketing and digital marketing on customer loyalty. The findings suggest that implementing these strategies can be beneficial for MSMEs in the chicken intestine chips industry in Kediri, as they can enhance customer loyalty and potentially lead to increased business success.